2011
DOI: 10.1128/jvi.01973-10
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aldehyde Dehydrogenase and Hsp70 in Suppression of White Spot Syndrome Virus Replication at High Temperature

Abstract: High temperature (32 to 33°C) has been shown to reduce mortality in white spot syndrome virus (WSSV)-infected shrimps, but the mechanism still remains unclear. Here we show that in WSSV-infected shrimps cultured at 32°C, transcriptional levels of representative immediate-early, early, and late genes were initially higher than those at 25°C. However, neither the IE1 nor VP28 protein was detected at 32°C, suggesting that high temperature might inhibit WSSV protein synthesis. Two-dimensional gel electrophoresis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…For example, a previous study found that WSSV could consistently promote the synthesis of CRT by 3-fold, regardless of the temperature in a culture of Penaeus monodon (25). Similarly, another report found that CRT protein expression in the stomach of L. vannamei was significantly upregulated by WSSV infection (27).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, a previous study found that WSSV could consistently promote the synthesis of CRT by 3-fold, regardless of the temperature in a culture of Penaeus monodon (25). Similarly, another report found that CRT protein expression in the stomach of L. vannamei was significantly upregulated by WSSV infection (27).…”
Section: Discussionmentioning
confidence: 91%
“…4A). Nevertheless, the CRT protein drew our attention, because it was found to be: 1) clearly induced by WSSV infection in many organisms (25)(26)(27); 2) present in the extracellular matrix or on the cell surface, as well as in the endoplasmic reticulum as a chaperone (28); and 3) the receptor of mammalian MBL (29). This background information prompted us to further study the potential role of CRT in the MjsvCL-mediated virus infection.…”
Section: Viral Infection-promoting Activity Of Mjsvcl Is Dependent Onmentioning
confidence: 99%
“…In addition to that, induction of Hsp70 gene transcription at 32°C during WSSV infection suggests a connection between this gene and WSSV resistance in shrimp (Lin et al, 2011). In the present study, we have challenged a virus-free population with WSSV, and no significant genetic differences were found between the dead and surviving groups.…”
Section: Discussionmentioning
confidence: 89%
“…One of the most studied HSPs is the Hsp70, for its ubiquity and essential role in the cell (Morano, 2007). In Litopenaeus vannamei the transcription of the Hsp70 gene is induced at 32°C during white spot syndrome virus (WSSV) infection, suggesting a functional role of HSPs in suppressing virus replication and reducing mortality in WSSV-infected shrimps (Lin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…dsRNAi technology is widely used in shrimp to systemically suppress expression of a target gene (25)(26)(27)(28), and here, to investigate the importance of ICP35 to WSSV pathogenesis, we used this technology to knock down the expression of icp35 during WSSV infection.…”
Section: Wssv Icp35 Is a Highly Expressed Nonstructural Proteinmentioning
confidence: 99%